Biodegradation of aliphatic hydrocarbon by indigenous fungi isolated from used motor oil contaminated sites - Husaini, A.; Roslan, H.A; Hii, K.S.Y.; Ang, C.H. (Springer Netherlands, 2008)
Eighteen indigenous fungal isolates has been successfully isolated from samples of used motor oil, top five centimetres of soil and drainage water contaminated with used motor oil. All of the pure fungal isolates obtained were identified, characterized and subjected to preliminary screening by evaluating the average growth rate of each fungal isolates on minimal media containing 1% (v/v) used motor oil. Trichoderma asperellum strain TUB F-1067 (SA4), Trichoderma asperellum strain Tr48 (SA5), Trichoderma asperellum strain TUB F-756 (SA6), Penicillium species (P1), and Aspergillus species (P9) were further selected for their hydrocarbon biodegradation potential. Among these five fungal isolates selected, P1 strain presented a significant degree of degradation by degrading almost all of the n-alkanes (n-C-15 to n-C-23 range) present in the used motor oil, thus of greater potential in degrading the aliphatic hydrocarbon compounds of used motor oil.